MODERN DIAGNOSIS OF TETRALOGY OF FALLOT (Modern education and development, 2025)
Instrumental diagnostics of tetralogy of Fallot includes PCG, electrocardiography, ultrasound of the heart, chest X-ray, catheterization of the heart chambers and ventriculography. Surgical treatment of tetralogy of Fallot can be palliative (placing intersystem anastomoses) and radical (complete surgical correction of the defect). Tetralogy of Fallot is a combined congenital anomaly of the heart, characterized by stenosis of the outflow tract of the right ventricle, a defect of the interventricular septum, dextroposition of the aorta and hypertrophy of the right ventricular myocardium. Clinically, tetralogy of Fallot is manifested by early cyanosis, developmental delay, shortness of breath and dyspnea-cyanotic attacks, dizziness and fainting.